Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Study on mining pressure law and its influencing factors of deep super-long gangue backfilling working face - Yang Kang; Zhang Qiang; Zou Mingjun; Cui Pengfei; Zong Tingcheng; Zhang Bin; Lv Haonan; Bai Yu; Deng Panbo; Li Jiang (Arabian Journal of Geosciences, 2026)

Reassessing the spatial and temporal evolution of the Southeast Asian Tin Belt: Insights into recurrent tin mineralization - Xiang Sun; Mingjun Zheng; Tong Pei; Pete Hollings; Xiaobo Si; Rongqing Zhang; Jun Deng (Earth-Science Reviews, 2025)

Versatile defect-laden boronizing hard carbon for superior sodium-ion battery efficacy - Jiayi Wen; Cheng Liu; Mingjun Jing; Dan Li; Honghui Hu; Huaxin Liu; Tianjing Wu; Lanhua Yi; Yong Pei; Xue Zhong; Wentao Deng; Guoqiang Zou; et al. (Chemical Engineering Journal, 2025)

Water-in-eutectogel electrolytes for scalable solid-state electrochromic devices - Jianbo Deng; Mingjun Chen; Xiang Zhang; Hulin Zhang; Liping Hu; Shuokun Sun; Jiupeng Zhao; Yao Li (Chemical Engineering Journal, 2025)

Application of biomass energy in titanomagnetite reduction for Fe/Ti recycling: Overcoming the challenge of iron grain growth - Lingyun Yi; Xiaoshuai Shen; Yang Shu; Bing Deng; Qiang Zhong; Zhiwei Peng; Mingjun Rao; Guanghui Li; Tao Jiang (Fuel, 2025)

Correction to: Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

A sensitive geometric self-calibration method and stability analysis for multiview spaceborne SAR images based on the range-Doppler model - Lina Yin; Mingjun Deng; Yin Yang; Yunqing Huang; Qili Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

Defective carbon-bridged Cu sites to boost oxygen reduction reaction in neutral zinc-air batteries - Tianjing Wu; Honghui Hu; Yufeng Wu; Mingjun Jing; Zhanpeng Chen; Fang Chen; Yansong Bai; Dan Li; Sheng Zhang; Lijie Liu; Wentao Deng; Hongshuai Hou; et al. (Chemical Engineering Journal, 2024)

Synthesis, Structure and Luminescence Properties of Mn-doped MgAl2O4 Red-Emitting Phosphors with Varying Sintering Temperature - Jiahao Zha; Chongjun He; Fangzhou Chen; Hongwei Wang; Biao Dong; Lijuan Liu; Mingjun Xia; Chenguang Deng; Qian Li; Yuangang Lu; Huiting Chen (Journal of Fluorescence, 2024)

A Synthetic Steroid 5α-Androst-3β, 5, 6β-triol Alleviates Radiation-Induced Brain Injury in Mice via Inhibiting GBP5/NF-κB/NLRP3 Signal Axis - Ke Zhong; Kejia Liu; Yu Song; Sitai Chen; Xia Hu; Ruiqi Xue; Xueying Ma; Shaojian Li; Jingwen Yang; Zhenhong Deng; Xiaoqiu Zhu; Mingjun Yuan; et al. (Molecular Neurobiology, 2024)

Highly efficient photocathodic cascade material for constructing sensitive photoelectrochemical biosensor - Mingjun Xiao; Qian Xiong; Chaoju Yang; Hanmei Deng; Ruo Yuan; Yali Yuan (Analytica Chimica Acta, 2023)

Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency - Peiyan Yang; Peng Zhang; Yali Deng; Yinghao Liao; Xinxin Guo; Mingjun Sun; Lihong Yin; Ran Liu (Environmental Pollution, 2023)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Bisphenol A adsorption behavior on soil and biochar: impact of dissolved organic matter - Yawen Deng; Caixia Yan; Minghua Nie; Mingjun Ding (Environmental Science and Pollution Research, 2021)

Occurrence, seasonal variation and environmental impact of phosphorus flame retardants in a large scale wastewater treatment plant - Zhineng Liu; Mingjun Deng; Qihang Wu; Dave T. F. Kuo; Lixi Zeng; Zhu Wang; Ying Zhang; Xinyu Liu; Shengyu Liu; Junyan Liang; Xiaodong Hu; Bixian Mai (Environmental Science and Pollution Research, 2019)

Assessing pollution and risk of polycyclic aromatic hydrocarbons in sewage sludge from wastewater treatment plants in China’s top coal-producing region - Qihang Wu; Zhineng Liu; Junyan Liang; Dave T. F. Kuo; Shejun Chen; Xiaodong Hu; Mingjun Deng; Haozhi Zhang; YueHan Lu (Environmental Monitoring and Assessment, 2019)

Planar block adjustment and orthorectification of Chinese spaceborne SAR YG-5 imagery based on RPC - Taoyang Wang; Guo Zhang; Deren Li; Ruishan Zhao; Mingjun Deng; Tong Zhu; Lei Yu (International Journal of Remote Sensing, 2018)

Supplementary studies on Myxobolus tsangwuensis Chen, 1954 (Myxozoa: Myxosporea) infecting the gills of common carp Cyprinus carpio (L.): molecular and histological data - Mingjun Huang; Yang Liu; Luo Jia; Yanhua Zhai; Qiong Deng; Zemao Gu (Acta Parasitologica, 2014)
Myxobolus tsangwuensis Chen, 1954 is a common parasite infecting the gills of common carp Cyprinus carpio (L.). It was described simply in the original description and its molecular data was absent, which makes the accurate diagnosis challenging. Here we supplemented its description based on the morphological, histological and molecular data. It was characterized by the presence of small round or ellipsoidal plasmodia in the gills of host and histology showed the plasmodia developed in the capillary network of the gill lamella. Mature spores of M. tsangwuensis were ellipsodal in frontal view and lemon shaped in lateral view, averaging 11.2 ± 0.7 (10.2–12.5) μm × 9.3 ± 0.3 (8.5–10.0) μm × 6.2 ± 0.4 (5.5–7.0) μm. Spores valves were symmetrical and smooth. Occasionally, a small intercapsular appendix was observed. Two polar capsules were pyriform with different sizes, measuring 5.0 ± 0.2 (4.4–5.3) μm × 3.1 ± 0.1 (2.9–3.5) μm and 3.9 ± 0.2 (3.4–4.3) μm × 2.5 ± 0.2 (2.0–2.8) μm, respectively. Polar filaments coiled five to seven turns in large polar capsule and three to four turns in the small polar capsule. Some spores were surrounded by the mucous envelope that was not recorded in the original description. Molecular analysis revealed that the present SSU rDNA sequences did not match any available sequences in GenBank and phylogenetic analysis showed M. tsangwuensis was sister to M. basilamellaris and M. musseliusae.